Asupan energi, aktivitas fisik, persepsi orang tua, dan obesitas siswa dan siswi SMP di Kota Yogyakarta - Elisabeth Pampang; Martalena Br Purba; Emy Huriyati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2009)
Backgound: Juvenile obesity is becoming a global problem. The high prevalence of juvenile obesity is due to an inadequate physical activity and an imbalance of nutritional intake. The roles of parent are significant in the incidence of obesity; therefore their understanding on the prevention of obesity is necessary. Findings of some studies in Yogyakarta show that 7.9 % of adolescents are approaching obesity.Objective: To assess the relationship between energy intake, physical activities, parental perception, and the status of obesity among students grade 7 to 9.Method: This study used cross sectional design. The samples were students grade 7 to 9 of Yogyakarta Municipal City including those who were obese and non-obese. The respondents were recruited as many as 230 students; chi square (χ²) test and significant level of 95%, were used to analyze the difference between obese and non-obese group.Results: This study found that energy intake correlated with obesity (p < 0.05). Moreover, physical activity significantly correlated with obesity (p < 0.05). Nevertheless, parental perception did not significantly correlate with obesity (p > 0.05).Conclusion: Physical activity and energy intake had an association with obesity status among students grade 7 to 9 in Yogyakarta Municipal City. But parental perception had no association with obesity among the respondence.